(untitled) (Pulse, 2014)
Background Diabetic nephropathy is a chronic micro vascular complication of poorly controlled diabetes mellitus (DM), leading to end stage renal disease (ESRD). Control of DM is monitored by HbA1c. There are two early markers - to assess early renal impairment: Microalbuminuria (MA) & Glomerular Filtration Rate (GFR). Estimation of MA - needs 24 hours collection of urine. GFR is clinically assessed by creatinine clearance rate (CCR) at the same time for accurate estimation of GFR which also needs 24 hours urine collection. Faulty timing and non compliance for 24 hours urine collection - may give erroneous results. MA is better reflected by spot urine urinary albumin-creatinine ratio (ACR). Some formula based calculation of GFR, called estimated GFR (eGFR) are well correlated with CCR which needs only single blood sample for S.Creatinine (S.Cr). For example one such formula is Cockroft-Gault (C-G) formula. Objective To evaluate the association of HbA1c with urinary ACR and eGFR in Type 2DM. Design It was a cross sectional study carried out in the department of Biochemistry, Sylhet MAG Osmani Medical College, from July 2010 to June 2011. Methods Fifty (50) known type 2 DM patients of 40-60 years age were evaluated dividing them on the basis of HbA1c (<8%,>8%), duration of DM (>5 years, <5 years), normotensives or hypertensives. FBS, S.Cr, Urinary Albumin & Creatinine were estimated. eGFR and urinary ACR were calculated. Results were expressed as mean ± SD. Data were analyzed with SPSS software version (12.0). Unpaired t test and Pearsons correlation tests were performed as tests of significance. Value of p<0.05 was the level of significance. Results Significant difference of S.Cr & HbA1c was found between study groups on HbA1c<8% and >8%. DBP was significantly raised in hypertensive type 2 DM. Duration of DM did not show significant correlation with renal functional parameters. Serum Creatinine & U.ACR had significant positive correlation with HbA1c>8% and only with ACR but not with S.Cr in study subjects having HbA1c<8%. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20183 Pulse Vol.5 January 2011 p.6-11